PEMBENTUKAN KARAKTER NASIONALISME MELALUI PENANAMAN NILAI-NILAI MALAQBIQ PADA PESERTA DIDIK DI SMAN 1 TINAMBUNG - Indah Permatasari; Rifdan Rifdan; Andi Aco Agus (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2024)
This research aims to find out: (1) Civics teachers' efforts in the process of nationalism character building through the cultivation of malaqbiq values in students at SMAN 1 Tinambung. (2) The inhibiting factors in the process of nationalism character building through the cultivation of malaqbiq values in students at SMAN 1 Tinambung. This research is a qualitative research with descriptive qualitative approach, the type of data used in the research is the type of primary data and secondary data. Data collection techniques were obtained through interviews and documentation. Data analysis used is data reduction, data presentation and conclusion drawing.The results showed that (1) The efforts of Civics teachers in the process of building the character of nationalism through instilling malaqbiq values in students, consist of: (a) teacher example, (b) getting used to the application of malaqbiq values in the school environment, and (c) internalizing malaqbiq values in the learning process. (2) inhibiting factors consist of globalization and domicile of origin of students.